1966
DOI: 10.1136/oem.23.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Excretion of Diquat and Paraquat in Rats

Abstract: The fate of 14C-labelled diquat and paraquat after oral and subcutaneous administration of single doses has been studied in the rat. By both routes of administration the radioactivity usually appears in the excreta within two days. In a few cases a small amount is excreted in the urine on the third day or in faeces on the fourth day. After an oral dose of paraquat no radioactivity could be detected in bile, and with diquat less than 5% of the dose appeared in bile within 24 hours. Both diquat and paraquat are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 2 publications
4
53
0
Order By: Relevance
“…It is poorly absorbed from the gut. The bulk of an oral dose is found in feces, whereas after subcutaneous dose, most of it is found in the urine and little or none in the feces (Daniel and Gage 1966).…”
Section: Discussionmentioning
confidence: 99%
“…It is poorly absorbed from the gut. The bulk of an oral dose is found in feces, whereas after subcutaneous dose, most of it is found in the urine and little or none in the feces (Daniel and Gage 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the metabolism of all these compounds, except morfamquat, have been reported in the literature. Daniel & Gage (1966) found only unchanged paraquat and diquat in the urine of intact rats given these compounds subcutaneously, and decamethonium has been reported to be excreted unchanged in the urine by rabbits (Broen Christensen, 1967), cats (Luthi & Waser, 1965) and humans (see Paton & Zaimis, 1952). Dimethyltubocurarine labelled with 14C in four of its methyl groups has been examined by Marsh (1952), whose results suggest that the compound is largely excreted unchanged in the urine after injection into guinea pigs, but when injected into rats the compound is excreted in the urine largely as unidentified metabolites, with a small amount of 14C appearing in the expired air in an unidentified form.…”
Section: Discussion Metabolismmentioning
confidence: 99%
“…The amount of [14C]diquat or [(4C]paraquat in the eluate from the column was determined both from the '4C content of portions (0.2ml) of the eluate and by colorimetric analysis as described by Daniel & Gage (1966).…”
Section: Separation Of Diquat and Paraquat From Urinementioning
confidence: 99%
See 1 more Smart Citation
“…When rats ingested toxic amounts of PQ (either accidentally or voluntary), the initial absorption occurred in the small intestine where the amount absorbed by the stomach was negligible, especially if there was parallel food intake, and the majority was excreted in the urine and feces (Daniel & Gage, 1966). It can also be absorbed and causes damage when it contacts with the skin, especially when there was a previously damaged area that would cause an abrasion contact zone (J. G. Smith, 1988).…”
mentioning
confidence: 99%